ACR Appropriateness Criteria® Resectable Pancreatic Cancer. (April 2017) - Jones, William E.; Suh, W. Waren; Abdel-Wahab, May; Abrams, Ross A.; Azad, Nilofer; Das, Prajnan; Dragovic, Jadranka; Goodman, Karyn A.; Jabbour, Salma K.; Konski, Andre A.; Koong, Albert C.; Kumar, Rachit; et al.
Abstract : Management of resectable pancreatic adenocarcinoma continues to present a challenge due to a paucity of high-quality randomized studies. Administration of adjuvant chemotherapy is widely accepted due to the high risk of systemic spread associated with pancreatic adenocarcinoma, but the role of radiation therapy is less clear. This paper reviews literature associated with resectable pancreatic cancer to include prognostic factors to aid in the selection of patients appropriate for adjuvant therapies. The American College of Radiology Appropriateness Criteria are evidence-based guidelines for specific clinical conditions that are reviewed annually by a multidisciplinary expert panel. The guideline development and revision include an extensive analysis of current medical literature from peer reviewed journals and the application of well-established methodologies (RAND/UCLA Appropriateness Method and Grading of Recommendations Assessment, Development, and Evaluation or GRADE) to rate the appropriateness of imaging and treatment procedures for specific clinical scenarios. In those instances where evidence is lacking or equivocal, expert opinion may supplement the available evidence to recommend imaging or treatment.